Phylogeny of Gracilariaceae (Rhodophyta): evidence from plastid and mitochondrial nucleotide sequences. Issue 2 (12th March 2015) - Lyra, Goia de M.; Costa, Emmanuelle da S.; de Jesus, Priscila B.; de Matos, João Carlos G.; Caires, Taiara A.; Oliveira, Mariana C.; Oliveira, Eurico C.; Xi, Zhenxiang; Nunes, José Marcos de C.; Davis, Charles C.; Müller, K.
<x xml:space="preserve">Abstract</x> Gracilariaceae are mostly pantropical red algae and include ~230 species in seven genera. Infrafamilial classification of the group has long been based on reproductive characters, but previous phylogenies have shown that traditionally circumscribed groups are not monophyletic. We performed phylogenetic analyses using two plastid (universal plastid amplicon and rbcL) and one mitochondrial (cox1) loci from a greatly expanded number of taxa to better assess generic relationships and understand patterns of character distributions. Our analyses produce the most well‐supported phylogeny of the family to date, and indicate that key characteristics of spermatangia and cystocarp type do not delineate genera as commonly suggested. Our results further indicate that Hydropuntia is not monophyletic. Given their morphological overlap with closely related members of Gracilaria, we propose that Hydropuntia be synonymized with the former. Our results additionally expand the known ranges of several Gracilariaceae species to include Brazil. Lastly, we demonstrate that the recently described Gracilaria yoneshigueana should be synonymized as G. domingensis based on morphological and molecular characters. These results demonstrate the utility of DNA barcoding for understanding poorly known and fragmentary materials of cryptic red algae.